2019
DOI: 10.1242/dev.172866
|View full text |Cite
|
Sign up to set email alerts
|

The central nervous system acts as a transducer of stress-induced masculinization through corticotropin-releasing hormone B

Abstract: Exposure to environmental stressors, such as high temperature (HT), during early development of fish induces sex reversal of genotypic females. Nevertheless, the involvement of the brain in this process is not well clarified. In the present work, we investigated the mRNA levels of corticotropin-releasing hormone b (crhb) and its receptors (crhr1 and crhr2), and found that they were upregulated at HT during the crucial period of gonadal sex determination in medaka. In order to clarify their roles in sex reversa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 67 publications
(97 reference statements)
6
27
0
Order By: Relevance
“…The down-regulation of 11 β -hydroxysteroid dehydrogenases hsd11b1-like can indicate a shift from cortisone-cortisol regeneration (Morgan et al, 2014). These expression patterns suggested that cortisol might cross-talk with steroidogenesis to mediate sex reversal under high temperature, which coincide with the study in pejerrey and medaka (Fernandino et al, 2012; Fermandino et al, 2013; Castañeda Cortés et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…The down-regulation of 11 β -hydroxysteroid dehydrogenases hsd11b1-like can indicate a shift from cortisone-cortisol regeneration (Morgan et al, 2014). These expression patterns suggested that cortisol might cross-talk with steroidogenesis to mediate sex reversal under high temperature, which coincide with the study in pejerrey and medaka (Fernandino et al, 2012; Fermandino et al, 2013; Castañeda Cortés et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…The hypothalamic–pituitary–adrenal (HPA) axis in reptiles, birds and mammals or inter‐renal (HPI) axis in fish and amphibians has a role in sex determination in a range of taxa [see reviews in Goikoetxea, Todd & Gemmell () and Geffroy & Douhard ()]. Among gonochoristic (single‐sex) fish, cortisol‐mediated sex determination in response to temperature is well supported by experimental application of cortisol (Hattori et al ., ; Hayashi et al ., ; Castañeda Cortés et al ., ; Miller et al ., ). Cortisol has not yet been experimentally demonstrated to be a mediator of sex change in sequentially hermaphroditic teleost fish, but transcriptomic evidence suggests cortisol upregulation, supporting a role for the HPI axis in the repression of aromatase and the regulation of downstream epigenetic effectors of gene regulation (Fernandino et al ., ; Solomon‐Lane, Crespi & Grober, ; Goikoetxea et al ., ; Todd et al ., ).…”
Section: Connections Between Care Status and Sex Determinationmentioning
confidence: 98%
“…[ 88 ] A recent study by Cortés and colleagues shows a strong link between the activity of the HPA axis during the gonadal determination period and masculinization in medaka ( Oryzias latipes ). [ 89 ] They demonstrated upregulation of one variant of corticotropin‐releasing hormone ( crhb ) and its receptors ( crhr1 and crhr2 ) under the stress condition (high temperature). The knockout of these receptors led to a loss of sensitivity to the stressor and inhibition of sex reversal (masculinization of XX females).…”
Section: How Does Esd Work? Hypotheses Involving Stresses Of Various mentioning
confidence: 99%